Amplicon and Cas9-targeted nanopore sequencing of Varroa destructor at the onset of an outbreak in Australia - McFarlane, Gus R.; Robinson, Katie L.; Whitaker, Kim; Webster, John; Drysdale, Lauren; Brancalion, Lillian; Webster, Ashlea; O’Rourke, Brendon; Bogema, Daniel R. (Frontiers in Bee Science, 2024)
Varroa destructor is a major pest of European honey bees (Apis mellifera), causing significant economic and welfare impacts. Australia remained the last continent free from V. destructor. In June 2022, a detection of V. destructor was reported in sentinel colonies at the Port of Newcastle, Australia. Rapid and accurate identification of the species was critical for timely response and management. In this case study, two Nanopore DNA sequencing methods, PCR amplicon sequencing and Cas9-targeted sequencing, were used to rapidly diagnose the species and mitochondrial haplotype of Varroa mites in parasitized colonies. Nanopore PCR amplicon sequencing provided molecular identification of the species and halogroup determination within 24 hours based on a 458 bp amplicon of the mitochondrial Cytochrome c oxidase subunit I (COXI) gene. We also developed and applied a Cas9-targeted Nanopore sequencing technique that used eight guide RNAs to enrich for 5240 bp of the mitochondrial genome. This method delivered richer data for identification within the same timeframe. Our results underscore the efficacy of Nanopore amplicon sequencing and represent the first reported application of Cas9-targeted Nanopore sequencing within a biosecurity framework. These findings enhance the repertoire of diagnostic tools available for biosecurity applications.